Analisis Penerapan Sistem Rekam Medis Elektronik di Rumah Sakit Mitra Sejati Kota Medan - Suryani Suryani; Vicky Arfeni Warongan; Aulia Dini Ayuningtias; Alesia Lorenzza Sinaga (Pusat riset dan Inovasi Nasional, 2025)
Advances in science and technology have significantly improved and facilitated the work of health professionals. One example is the transition from manual medical records to Electronic Medical Records (EMDR). At Mitra Sejati Hospital, the implementation of EMR still uses manual and electronic methods, so it is not in accordance with the Minister of Health Regulation Number 24 in 2022. This study aims to analyze the implementation of EMR in the mitra sejati hospital on the regulation. The research method used is descriptive qualitative, with observations made using checklist sheets to evaluate the SIMRS application. The research subjects included doctors, nurses, radiology, IT officers, and medical record officers, each represented by one participant. The results of the study showed that the implementation of EMR at Mitra Sejati Hospital was in accordance with the Minister of Health Regulation Number 24 in 2022 about filling in clinical information, inputting financing claim data, and storing EMR. However, the implementation of patient registration, EMR data distribution, information processing, quality assurance, and transfer of EMR contents were not fully in accordance. This discrepancy indicates that the implementation of EMR in the hospital was not fully in accordance with the regulations. To address this gap, special efforts are needed to improve technical systems and staff training, so that it can ensure full compliance with regulations and optimize the function of the EMR.